Caracterizacion de la variabilidad de una poblacion de mejora de Juglans regia L. - Alfonsin, P.=700 1 Abuin, M.; Diaz, R.; Fernandez-Lopez, J.
(En, Es)
ilus., 43 ref.
Keywords: JUGLANS REGIA; VARIACION GENETICA; FITOMEJORAMIENTO; IDENTIFICACION; ISOENZIMAS; ESPAÑA; NOPAL